Upaya Meningkatkan Kualitas Pertimbangan Audit Melalui Self_Review: Kasus Going Concern Perusahaan - I Wayan Suartana (The Indonesian Journal of Accounting Research, 2013)
This study examines self review as the debiasing mechanisms that can reduce the recency effect and improve judgment quality. Judgment quality is independent of outcomes. In an uncertain environment a bad outcome may result even though the judgment process is “good” in the sense that all relevant information is properly considered (Kennedy, 1993). Hogart and Einhorn (1992) propose and test a descriptive model of belief adjustment. They posit that individuals are sequential processors of information who employ an anchoring and adjustment strategy to incorporate new evidence in an evaluation task. One important prediction of the model is that order, in which a short series of complex, mixed evidence is evaluated, leads to a recency effect. Little research has been done on the issues of debiasing recency effect in an audit environment. Such research is necessary since the use of disproportional heuristic in decision making will lead towards an error.  The results show that self review mechanisms significantly reduces errors in the evaluation of going concern.